Sociological Method. A Comparative Historical Analysis - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2006)
The aim of the article is to explore the concept of sociological method by specifying the historical aspects of classical sociological thought. Sociological method is best seen as one of the chief heirs of the Enlightenment: it can be understood first of all as the historical realisation of the Enlightenment’s conception of a measurement and verification. Nevertheless, from its inception, sociology has been a confluence of many methodological streams. The concept of method is in fact highly ambiguous.This article offers a critical examination of the methodological modifications throughout the history of sociological thought. A central thesis of this article is that the very idea of method cannot be separated from the idea of meta-method.
Keywords: method; sociology; experimental science; methodology